Las humanidades - Barceló, Joaquín (Revista Chilena de Humanidades, 2015)
The author examines the past and present of the Humanities, objectives, situation vis-a-vis progress and practica utility. He points out their social and political responsibiiities as sources to orient the incessant structuring of a world with human dimensions, harmonious and free, through the practice of the Humanities in daily life.